URGENSI KECERDASAN BAHASA DALAM PENDIDIKAN ISLAM - Rozi, M. Asep Fathur (e-Journal STAI Muhammadiyah Tulungagung, 2014)
Intelligence language is ability that deals with said / language written or spoken. partly the subject matter at school associated with wit this intelegence. Urgency intelligence languages in islamic education, can be seen from some method of teaching. Among them are hiwar method, tale method, amtsal method, ibrah and mauâidzah method. Language used by someone to reflect the state of soul and personality someone, hence writers convinced, intelligence that language is window early for someone to master science another.